Simultaneous ice and transcutaneous electrical nerve stimulation decrease anterior knee pain during running but do not affect running kinematics or associated muscle inhibition. (February 2020) - Kwon, Sunku; Bruening, Dustin A.; Morrin, Steven J.; Kunz, Dillon M.; Hopkins, J. Ty; Seeley, Matthew K.
Abstract: Background: Runners often experience anterior knee pain and this pain is associated with altered running neuromechanics. The purpose of this study was to examine potential therapeutic benefits (reduced pain and restored running neuromechanics) of simultaneously applied ice and transcutaneous electrical nerve stimulation on experimentally-induced anterior knee pain. Methods: Nineteen healthy subjects completed a sham and treatment data collection session. For both sessions, hypertonic saline was infused into the infrapatellar fat pad for approximately 80 min to induce experimental anterior knee pain. Perceived pain levels were measured every two minutes and running neuromechanics were recorded at four time points: pre-pain, pain before treatment, pain immediately post-treatment, and pain 20 min post-treatment. Findings: The saline infusion significantly increased perceived knee pain from 0 to 2.8 cm. The ice/transcutaneous electrical nerve stimulation treatment significantly reduced perceived knee pain by 35%, six minutes after the treatment initiation. Perceived knee pain remained reduced until eight minutes after the treatment termination. The knee pain significantly decreased peak gluteus medius, vastus lateralis, and vastus medialis activation during running, each by an average of 17% plus/minus 6%; however, none of these decreases were resolved via the therapeutic treatment. Neither the knee pain nor the therapeutic treatment significantly affected peak gluteus maximus activation or peak hip adduction angle. Interpretation: The experimental pain model effectively produced anterior knee pain and decreased muscle activation during running. The simultaneous ice/transcutaneous electrical nerve stimulation treatment effectively decreased anterior knee pain, but did not restore running neuromechanics that were altered due to the pain. Highlights: An experimental pain model effectively produced anterior knee pain during running. Experimental knee pain inhibited hip and knee muscle activation during running. Ice with transcutaneous electrical nerve stimulation decreased this knee pain. The same therapy did not resolve pain-related muscle inhibition during running.